Nurturing Harmony from The Archipelago - Andriawan, Didik (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study aims to explain how the Qur’anic values of compassion (raḥmah) and tolerance (tasāmuḥ) can form an inclusive and civilized social ethic through a contextual interpretive approach. Employing Fazlur Rahman’s hermeneutical method, Jasser Auda’s systems-based maqāṣid al-sharī‘ah, and Hans Küng’s global ethic, this research analyzes four key verses: QS al-Anbiyā’ [21]:107, al-Ḥujurāt [49]:13, al-Baqarah [2]:256, and al-Mumtaḥanah [60]:8–9. Classical exegesis (al-Ṭabarī and Ibn Kathīr) is compared with Nusantara exegesis represented by Hamka, Quraish Shihab, and Mahmud Yunus to identify the shift from theological interpretation toward social praxis. The findings show that Tafsir Nusantara articulates a contextual and transformative Qur’anic social ethic. Raḥmah emerges as a normative foundation for justice, equality, and respect for diversity, while tasāmuḥ affirms religious freedom and peaceful coexistence. The integration of Rahman’s, Auda’s, and Küng’s theoretical frameworks constructs a universal, humanistic, and globally oriented Qur’anic ethical paradigm. These results demonstrate that Nusantara-rooted interpretations have significant potential to actualize the principle of raḥmatan lil-‘ālamīn within plural societies and to strengthen a culture of religious moderation